THE USE OF QUESTIONING TECHNIQUE TO ENHANCE STUDENTS’ SPEAKING ABILITY - Dedy Wahyudi (Indonesian Journal of Integrated English Language Teaching, 2017)
Due to Questioning and answering as the activities that cannot be separated from Daily communication, the difficulties of speaking English encountered by pre-service English teachers are highly required to be overcome. In addition, they are future English Teachers. This study, therefore, aims at enhancing students’ speaking ability through Questioning technique and finding out the factors that influence the change of students’ speaking ability. This study was a classroom action research, which was carried out in two cycles. The freshmen of English Education Department were the participants of the research. Based on the findings, it showed that Questioning Technique could improve students’ speaking ability in terms of accent, grammar, vocabulary, fluency, and comprehension, in which speaking fluency was the highest improvement of all. Moreover, it led the students to good self confidence and classroom participation. In short, the more the students use questioning technique, the better the students’ speaking ability is.